Puzzle: Cozy Kitchen - Warren Industries (Warren Industries / Lafayette, IN, 2000)
Cozy Kitchen jigsaw puzzle by RoseArt. This delightful 750-piece puzzle features a charming scene of a kitchen filled with numerous kitchen appliances.
8+
Keywords: Kitchen; Kitchen appliances